Management and quality indicators of diabetes mellitus in people with intellectual disabilities. (29th October 2012) - Taggart, L.; Coates, V.; Truesdale‐Kennedy, M.
Abstract Background People with intellectual disabilities (ID) are at a higher risk of developing diabetes compared with the non‐intellectually disabled population, as a consequence of genetic syndromes and because this cohort are more exposed to many of the identified risk factors. However, little is known about the management of diabetes in this population. The aim of this study was to examine the demographics, health and the diabetes quality of care indicators used with people with ID in one region of the UK. Methodology This was a quantitative study using a postal survey design. An anonymised questionnaire was posted to all community ID teams and supported living/residential facilities requesting information on the demographics, health and quality of care indicators for people with ID who have diabetes on their caseloads. Results In total 186 questionnaires were returned. Results showed that 125 people with ID had Type 2 diabetes (67%) and 61 people had Type 1 (33%). Significantly more people with Down syndrome and Autistic Spectrum Disorder had Type 1 diabetes. This study found that 6% had glycossylated glucose levels (HbA1c) greater than 9.5% and for 52% the levels were between 6.5% and 9.4%. Individuals reported to have poor glycaemic control were statistically more likely to have Type 1 diabetes and be younger, live with parents or independently and be obese. Results also illustrate that the national standards for good diabetes management were only partially met. Discussion Because of their enhanced predisposition for the development of diabetes this population merits particular attention with regards to screening for the onset of diabetes. The extent to which the quality of diabetes care indicators were achieved was variable but results suggest that for many people the indices were not met, that glycaemic control was poor, that only a quarter were of normal weight, that many were hypertensive and that almost a quarter had no record of their lipid levels. These findings provoke two important questions: first, who should be responsible for promoting diabetes management in this client group and second, how can service provision be tailored to better meet their needs? Greater collaborative working and education is required between ID services, primary healthcare and diabetes clinicians in order to promote the health and meet the quality indicators of diabetes care among this population.